If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x(7 + -4) = 0 Combine like terms: 7 + -4 = 3 9x(3) = 0 Reorder the terms for easier multiplication: 9 * 3x = 0 Multiply 9 * 3 27x = 0 Solving 27x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '27'. x = 0 Simplifying x = 0
| 75-v=266 | | 8x-2+4x=-4 | | 1.5x=1225 | | 15x-23x=-8 | | 75-(7x+9)=7(x+3)+x | | -2=2u+2 | | 576=18(x+18) | | (3z)+2+1=7 | | 167-x=249 | | 4x^2-7x-8=-x^2+4x+4 | | 7t^2-14t/4t^2-9 | | 10x+10=54 | | 5x*x-30x+y*y+10y+60=0 | | -7=3u+4u-29 | | -2=u-7 | | 2x^2+14x+49=30 | | -.75p-7=.25p | | 3x+24=-35 | | (X+1)(X+2)(X+3)(X+4)-5=0 | | 8m+4=25 | | 3=-16w | | 11x+19=129 | | 100/70=t/140 | | 1600100=76x | | 13y=6y+14 | | 8y+80=16 | | (8x-16)=729 | | 22x5-1/10 | | 3/4/1/12 | | 9h^2-20h=0 | | (X-2)(y+11.4)=360 | | 1/2x^2-12=-37 |